(3eONd GSJQGJjLj dJNWjW hJfejI GdehGQO GdHTQjIs - (3QGhjI(B, (3MSjfs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3GdEOGQI GdGSJQGJjLjI ddehGQO GdHTQjI,HYV eaGgje hCOhGJ GdJMdjd GdESJQGJjLj dJNWjW GdehGQO GdHTQjI,GSJQGJjLjGJ GdehGQO GdHTQjI aj Xd HYV GdJZjQGJ GdJfXjejI,GdESJKeGQ aj JfejI GdehGQO GdHTQjIs
Keywords: (3GOGQI GdGaQGOs; (3GdJNWjWs; (3Gdbhi GdYGedIs